Enhanced Conductivity of Multilayer Copper–Carbon Nanofilms via Plasma Immersion Deposition - Haotian Weng; Xiwu Zhang; Xuan Liu; Yunhui Tang; Hewei Yuan; Yang Xu; Kun Li; Xiaolu Huang (Nano-Micro Letters)
Highlights With plasma immersion deposition technology, multilayer copper–carbon nanofilms were fabricated and conductivity can achieve up to 30.20% increase compared to pure copper. By applying effective medium theory, first-principles calculations, and density of states analysis, the critical roles of copper atom adsorption sites and electron migration pathways within the nanocarbon film were analyzed, elucidating the mechanism of the conductivity enhancement. Large-scale electrode coating equipment suitable for industrial production was developed.